Investigation of Alternative Mixed-Conducting Oxides for SOFC Anode Applications. (7th July 2017) - Thomas, Tony; Qi, He; Liu, Xingbo; Zondlo, John W.; Sabolsky, Edward M.; Hart, Richard
Abstract : A testing protocol has been developed to analyse the thermal redox behavior of newly developed anode materials for SOFC application. This is in an attempt to speed through the material development process, as development of new anode materials is time consuming, labor intensive and expensive. A simple push rod type dilatometer has been used in the characterisation of high temperature redox behavior of materials by automating the timely introduction of oxidizing and reducing atmosphere in order to simulate cell stack leak. By using the present test protocol, data like co-efficient of thermal expansion (CTE), volumetric change in the cell lattice, redox behavior (volumetric expansion or volumetric reduction) and number of redox cycles before material failure can be obtained. The testing protocol has been calibrated with commonly used SOFC materials like YSZ (8 mol% yttria doped), GDC (20 mol% Gd doped), La0.35 Sr0.65 TiO3 (LST) and also with LST/GDC (50/50 vol%) composite.